ANALISIS INOVASI PELAYANAN PERIZINAN JEMPUT BOLA DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN SEMARANG - Ida Wantri Hastuti; Susi Sulandari (Journal of Public Policy and Management Review, 2018)
Analysis of innovation of licensing service of ball picking at the One Stop Service and One Stop Service (DPMPTSP) of Semarang Regency on the back of poor service this is because the distance between subdistrict and location of Dinas are classified so that the service given by the society is hampered. Innovation pick up the ball is the solution of the problem is done by DPMPTSP Semarang regency. The purpose of this research is to explain the process of innovation to pick up the ball as well as to know the driving factors and the inhibiting factors of the innovation pick up the ball. The method used in this study is descriptive qualitative that is expected to provide a clear picture of the innovation process as well as driving factors and inhibiting factors. The result of this research is innovation process of ball pick consist of knowledge stage, persuation stage, decision stage, implementation stage, confirmation stage. Driving factors of balloon innovation are political impetus, economic pressure and increased efficiency, pressure to improve service quality. While the inhibiting factors consist of reluctance to close down failed programs, existing technology, hampered culture and organizational structuring, no rewards or incentives, inability to face risks and change, short-term budgets and planning, risk aversion culture. The recommendation of this research is the use of technology in balloon innovation, employee training DPMPTSP in the use of technology, the addition of facilities and infrastructure as well as innovation activities more regular pickup ball done in order to achieve fast, efficient and effective service.